2012
DOI: 10.1021/bc300066a
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic, Biodistribution, and Biophysical Profiles of TNF Nanobodies Conjugated to Linear or Branched Poly(ethylene glycol)

Abstract: Covalent attachment of poly(ethylene glycol) (PEG) to therapeutic proteins has been used to prolong in vivo exposure of therapeutic proteins. We have examined pharmacokinetic, biodistribution, and biophysical profiles of three different tumor necrosis factor alpha (TNF) Nanobody-40 kDa PEG conjugates: linear 1 × 40 KDa, branched 2 × 20 kDa, and 4 × 10 kDa conjugates. In accord with earlier reports, the superior PK profile was observed for the branched versus linear PEG conjugates, while all three conjugates ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 26 publications
1
35
0
1
Order By: Relevance
“…Like chain length, the shape of PEG chains can influence the effect of PEGylation on circulation time of PEGylated proteins. Despite the fact that total PEG length was similar, the use of branched PEG chains (2 × 20 or 4 × 10 kDa) increased the serum half‐life of tumor necrosis factor‐alpha targeting VHH more than PEGylation with linear PEG chains (1 × 40 kDa), as studied in mice, rats, and cynomolgus monkeys …”
Section: Protein Modifications That Affect Pharmacokinetics and Tumormentioning
confidence: 99%
“…Like chain length, the shape of PEG chains can influence the effect of PEGylation on circulation time of PEGylated proteins. Despite the fact that total PEG length was similar, the use of branched PEG chains (2 × 20 or 4 × 10 kDa) increased the serum half‐life of tumor necrosis factor‐alpha targeting VHH more than PEGylation with linear PEG chains (1 × 40 kDa), as studied in mice, rats, and cynomolgus monkeys …”
Section: Protein Modifications That Affect Pharmacokinetics and Tumormentioning
confidence: 99%
“…Several branched and non-branched PEG structures have been evaluated for the effect on renal clearance. Enhanced PK profiles for branched PEG conjugates have consistently been described for therapeutic proteins in the literature [112114]. Recently for instance, single domain antibodies labeled with 2x20 kDa PEG were shown to be superior over 1x40 kDa and 4x10 kDa labeling without affecting the biological activity [114].…”
Section: Applications For Therapeutic Antibodiesmentioning
confidence: 99%
“…Enhanced PK profiles for branched PEG conjugates have consistently been described for therapeutic proteins in the literature [112114]. Recently for instance, single domain antibodies labeled with 2x20 kDa PEG were shown to be superior over 1x40 kDa and 4x10 kDa labeling without affecting the biological activity [114]. Biodistribution studies showed higher serum exposure of the antibody, though this was not the case for some tissues.…”
Section: Applications For Therapeutic Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Yamoka et al showed differences in tissue uptake for naked (non-protein attached) PEG molecules of different molecular weight after IV administration in mice (42,43). A recent case study with a PEGylated TNF-binding Nanobody suggested that the impact of the degree of PEG branching on tissue distribution may not necessarily parallel the impact on serum PK (48). In this study, mice were given a single IV injection of 125 I-labeled anti-TNF Nanobody conjugated to either linear or branched 40-kDa PEG and serum PK, and tissue penetration in normal mice was examined.…”
Section: Pegylationmentioning
confidence: 99%